Disciplina de Libras A/B na ufam - Gaspar, Márcio César Santos (Brasil, 2024)
This Final Course Work (TCC) explores the discipline of Libras A/B at the Federal University of Amazonas (UFAM) and its impact on the training of academics. The research was motivated by the researcher's experience as a student and monitor of the discipline, which sparked an interest in investigating and describing the perceptions of academics of the discipline of Libras A/B, investigating their motivations and the importance of this training for their professional development. It also aims to understand how students perceive Brazilian Sign Language and deafness, and how this understanding can influence the application of Libras in their daily professional practices. The research was conducted in two main stages: First, a survey was conducted via a form (Google forms) for the students of the institution. In the second stage, the responses of the respondents were analyzed, and a bibliographic analysis and documents that officialize the discipline in undergraduate courses were compared with the pertinent theoretical postulates. The results indicate that the discipline of Libras A/B can represent a differential in the curriculum of students, encouraging many to seek more training in the area. It was observed that the students understood the purpose of the discipline in their undergraduate and professional training, valuing and applying the knowledge acquired effectively.